Studying and Analyzing Operating Conditions of Hollow Fiber Membrane Preparation Process: A Review Paper - Rashad, Zaid (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
Polymeric hollow fiber membrane is produced by a physical process called wet or dry/wet phase inversion; a technique includes many steps and depends on different factors (starting from selecting materials, end with post-treatment of hollow fiber membrane locally manufactured). This review highlights the most significant factors that affect and control the characterization and structure of ultrafiltration hollow fiber membranes used in different applications. Three different types of polymers (polysulfone PSF, polyethersulfone PES or polyvinyl chloride PVC) were considered to study morphology change and structure of hollow fiber membranes in this review. These hollow fiber membranes were manufactured with different process conditions and a reasonable starting point for factors remained constant to study the changing effect of specific factors.